ANALISA KAPASITAS RUANG PARKIR PASAR MODERN KOTA PASIR PENGARAIAN - Khairul Fahmi (Universitas Pasir Pengaraian, 2014)
This study took place at Pasar Modern Pasir Pengaraian, the aim to determine characteristics which include parking accumulation, the volume of vehicle parking, parking duration, parking index and turnover of parking. The survey grouped on weekdays and holidays. The data obtained in the form of data registration numbers of vehicles consisting of a vehicle type cars (sedans, jeeps and pick-ups) and motorcycles.The result showed the maximum parking accumulation for motorcycles as many as 155 vehicles at a time interval 10:00 to 11:00 am, while on the car as much as 30 vehicles on the time interval 10:00 to 11:00 am. The majority of parking duration between 5-6 Hours. The maximum turnover rate for car parking occurs on a holiday at the clock 09:00 to 10:00 am for the motorcycle while going on holiday at 8:00 to 9:00am. Car parking for a maximum index of 21.429% on holiday while on the motorcycle of 55.537% on holidays. The amount of parking index value indicates that the parking capacity of Pasar Modern Pasir Pengaraian still able to accommodate parking demand that occurs at this time